Occupant behavior lifestyles in a residential nearly zero energy building: Effect on energy use and thermal comfort. (2nd October 2016) - Barthelmes, Verena M.; Becchio, Cristina; Corgnati, Stefano P.
Abstract : Occupant behavior is one of the most significant driving factors of uncertainty in the prediction of building energy use. Large performance gaps have been individuated between residential buildings with the same properties and similar climate conditions. Comfort criteria settings by the occupants and their interaction with the envelope and the systems directly affect the operation of buildings and related energy uses. This study employs building simulations to demonstrate the potential impact of occupant behavior lifestyles and different household compositions on energy use and thermal comfort conditions in a residential nearly zero energy building under-construction. In detail, occupant behavior was classified into three lifestyles: low consumer, standard consumer, and high consumer. The analysis considered energy-related behavioral patterns (regulation of heating and cooling set-points, energy use for equipment, lighting and domestic hot water, ventilation rates, regulation of window blinds) and highlighted key variables, which need to be addressed by decision-makers of behavioral change programs for conscious use of nearly zero energy buildings. While predictive studies concerning energy performance investigated mainly nearly zero energy building models that addressed the optimization of the building features themselves, this research reveals the urgent need of reference models related to human behavioral issues.